2020
DOI: 10.1055/s-0040-1713695
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Stress Patterns in Bone Around Implants for Different Abutment Angulations Under Axial and Oblique Loading in Anterior Maxillary Region—A Finite Element Analysis

Abstract: Introduction Replacing missing anterior teeth with a prosthesis that resembles natural form and function has always been challenging for a prosthodontist. Removable and fixed options both have been extensively studied and researched upon. In modern dentistry, implants have proved to be a more logical option for the same. The morphology of bone present in the premaxilla serves as guide to plan implant angulation during osteotomy. Factors such as age-related bone resorption, trauma or pathologic bone resorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…In the studies conducted by Clelland et al [33] and Papavasiliou et al [34], the simulation results demonstrated that stresses were concentrated in the cortical bone, and the magnitude of these stresses increased with increases in the abutment angulation. Interestingly, our research yielded similar results, with observed increases in stress values associated with higher abutment angulations [35][36][37][38]. Baggi et al [19] showed that the implant neck bears the maximum load due to contact stress.…”
Section: Discussionsupporting
confidence: 82%
“…In the studies conducted by Clelland et al [33] and Papavasiliou et al [34], the simulation results demonstrated that stresses were concentrated in the cortical bone, and the magnitude of these stresses increased with increases in the abutment angulation. Interestingly, our research yielded similar results, with observed increases in stress values associated with higher abutment angulations [35][36][37][38]. Baggi et al [19] showed that the implant neck bears the maximum load due to contact stress.…”
Section: Discussionsupporting
confidence: 82%